Effectiveness of Evidence-Based Measures on Nausea and Vomiting during First Trimester of Pregnancy - Asmaa I. Marak; Mona A. El-Sheikh; Eman M. S. Ahmed (Evidence-Based Nursing Research)
Context: Nausea and vomiting are the most common pregnancy symptoms that negatively affect many pregnant women. Severity varies from mild distaste for certain foods to more severe vomiting.